The start-up of a distribution of gourmet Coffee Bean company in Malaysia - Teoh, Kok Seong (2021)
Gridlock Coffee (M) Sdn Bhd is aiming to be registered in the Company Security Commission in Kuala Lumpur, Malaysia. Gridlock Coffee Malaysia will enter into the business of distributing of premium Coffee beans in the Food and Beverage industry for the segment of restaurants and café in Malaysia.